O trabalho do (a) Assistente social nos Centros de Atenção Psicossocial Álcool e Drogas/ CAPS AD : um estudo de revisão sistemática - Hertzog, Raquel Oliveira (2021)
Regarding history, the abusive use and/or dependence on alcohol and drugs had been approached from a biomedical point of view and through public security policies, in which other issues such as social, psychological, economic implications, etc. were not relevant in people's health care. With the disputes between emancipatory struggles of Psychiatric Reform and conservative logics, the hospital-centered model and the old asylums were being modified. This pattern of mental health care, from the 1970's manifestations of resistance, became the Psychiatric Reform Movement, a political process that, through various fields of struggle, begins to denounce the violence of asylums, the commodification of madness, the hegemony of a private assistance network and to collectively build a critique of the so-called psychiatric knowledge and the hospital-centered care model for people with mental disorders, with the response of substitute services, such as Psychosocial Care Centers, which are guided by care in freedom. With Ordinance No. 3,088, of 2011, CAPS AD – Center for Psychosocial Care for Alcohol and Drugs, becomes one of the points of health care in the care of people with alcohol and drug abuse, where social workers have as direction, the understanding of the movement of the real, of the contradictions and possibilities of contemporary society, in the search for the autonomy and guarantee of the rights of the subjects. The present dissertation has the objective to analyse the labour of social workers in the CAPS AD, through a systematic review study. Data collection occurred by searching the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel. Among the inclusion criteria are Brazilian theses and dissertations, from the graduate programs of social work, from 2003 to 2019, which researched the work of the social worker in the CAPS AD. The corpus of analysis consisted of seven academic productions: six master’s dissertations and one doctoral thesis. Data analysis was performed based on qualitative meta-synthesis, in which it was decided to analyze the empirical data of the interviews with social workers present in the dissertations and thesis. The research problem was: “how is the work of social workers in the Centers for Psychosocial Care for Alcohol and Drugs being developed, based on academic productions within the scope of postgraduate programs in social work?” The objectives of the study were: to point out challenges and potentials in the work of social workers developed at CAPS AD based on the interviews of the academic productions analyzed; to identify elements of the conjuncture analysis that stand out in the interviews of the academic productions studied, referring to the work of social workers; and to verify in the interviews of the academic productions if the work of social workers in CAPS AD presents articulation with the ethical-political project of the profession. The results obtained from the qualitative meta-synthesis of the works, showed the invisibility of the categories gender, race and generation. Another important issue observed in the corpus was the structural violence, which was identified through the multiple expressions of the social issue described in the interviews. It was concluded that the social workers develop their work in the CAPS AD with a perspective aligned with the Political Ethical Project of the Profession in most of the reports. However, in the discourse there are still some aspects related to prohibitionism, the homogenization of psi knowledge, and the need for professionals to deepen gender relations and gender identity in order to build more equitable and inclusive practices within the scope of the professional work of social workers in CAPS AD.